Improving the scientific and educational activities of a university teacher in the conditions of a new reality - Natalia Romanovna Turavets; Kurgansky Sergey Ivanovich; Alina Vyacheslavovna Skripkina; Ekaterina Gavrilovna Vakulenko; Vitaly V. Kistenev (Revista on line de Política e Gestão Educacional)
The article considers the issues of scientific and educational activity, the role and significance of scientific schools in this process; defines the main functions, tasks and requirements imposed on the activities of this scientific community; determines the diversification of research areas related to the industry specifics of the University of culture and arts. To meet the study’s aims, theoretical analysis, and systematization methods are utilized. Based on the results acquired, the utmost importance of scientific schools of a creative university is much deeper, for it indicates an understanding of their essence in the management of an educational institution, indicates an understanding of the fundamental factors for a systematic approach to the development of scientific potential of scientific and educational activities of the higher-education teaching staff of the Institute of Culture and Arts.